A Critical Assessment of the Asia Rebalance. (25th January 2019) - Katagiri, Nori
Abstract: While the Obama administration's Asia rebalance strategy received some praise from scholars and practitioners, it generated three problems that caused the USA to overlook many opportunities and neglect vital concerns. First, the strategy left Asia less stable by undermining US relations with China and smaller states in Southeast Asia. Secondly, it weakened America's influence outside Asia by committing fewer resources. Finally, the rebalance was executed out of a relatively small cadre of government officials, allowing primarily civilian agencies to dictate Asia policy and excluding key branches of government. Furthermore, although the strategy competed with the strategies of restraint and offshore balancing, it never had the solid support of any international relations theories, leaving few scholars to directly associate it with a theory. Ultimately, the rebalance's multiple logics prevented it from achieving intellectual hegemony in the American foreign policy discourse, and its substantive flaws and theoretical inconsistencies made difficult its acceptance as an enduring strategy in the Asia-Pacific region.